Abordagem transiente sobre os efeitos do amortecimento viscoelástico na estabilidade aeroelástica de estruturas aeronáuticas - Cunha Filho, André Garcia (2019)
Flutter is a kind of aeroelastic instability caused by the simultaneous interaction of aerodynamic, elastic and inertial forces upon a structure. In the design of1 an aircraft, flutter is always a major concern due to its high risk of structural collapse. The constant search for solutions intended to increase aircraft performance and consequently reduce environmental impacts has motivated the use of new concepts, such as high aspect ratio wings and the employment of new materials. However, those solutions become an important structural challenge, since they induce an increase of flexibility making the structure prone to flutter. Thus, the use of passive vibration control techniques, such as viscoelastic materials may be a feasible solution to increase the system aeroelastic performance as a result of its high structural damping rate. Automotive and aeronautical industries largely employ viscoelastic materials to mitigate noise and small vibrations. Little is known about the real effect of viscoelastic damping to reduce aeroelastic instabilities. In this scenario, aeroelastic models always involve high computational costs and introducing viscoelasticity within it may cause them to be unfeasible. Therefore, the creation and employment of computational low costs models capable of representing the dynamic behavior of aeroviscoelastic systems is a real challenge. The focus here is to create feasible aeroviscoelastic models by applying reduction model techniques and mathematically improving the existent ones. Three kinds of aeroviscoelastic systems has been studied: aeronautical panels, a non linear typical section and a representative high aspect ratio wing. For those, three aerodynamic theories are used: the Piston Theory for panels, the Unsteady Wagner’s Theory and the Unsteady Strip Theory. Except for the panel models, experimental validation were carried through in wind tunnel.